Application de la carte interculturelle en tant que média d’apprentissage interculturel indonésien-français sur la compréhension écrite des lycéens de l’hospitalité XI SMK Negeri 3 Magelang - Taffitia Risnanti Yusuf; Sri Handayani (Universitas Negeri Semarang, 2025)
This study is motivated by one of the objectives of French language subjects in high school within the independent curriculum, specifically regarding cross-cultural understanding. However, this goal has not been fully met at SMK N 3 Magelang because cross-cultural learning is only inserted during the lesson. The purpose of this study was to determine the learning outcomes and knowledge of students after using the Indonesian French cross-cultural quartet media in reading skills. This research employs an experimental case study design with 30 respondents from SMK N 3 Magelang. The methods used to collect data were tests and documentation. The test consisted of 20 multiple-choice questions. The results of this study indicate that the application of cross-cultural quartet media in class XI Hospitality students has a good effect. This can be seen from the overall percentage of students passing the Indonesian French cross-cultural knowledge test, which is as high as 90%, with an average score of 82.83 obtained by students. It can be concluded that the application of cross-cultural quartet media yields good learning outcomes and enhances the cross-cultural knowledge of Indonesian French in reading skills among XI Hospitality students of SMK N 3 Magelang after the media is accepted.